2011
DOI: 10.1177/1040638711425595
|View full text |Cite
|
Sign up to set email alerts
|

Comparing citrated native, kaolin-activated, and tissue factor–activated samples and determining intraindividual variability for feline thromboelastography

Abstract: Abstract. Thromboelastography (TEG) is a point-of-care whole blood test of hemostasis. While TEG is becoming more widely used in veterinary medicine, few studies describe the use of TEG in cats. The objectives of the current study were to: 1) document the range of TEG variables produced in healthy cats using 3 sample types (citrated native, kaolin-activated, and tissue factor-activated), and 2) determine if there was a significant difference between 2 separate samples obtained from individual healthy cats on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 18 publications
1
35
0
Order By: Relevance
“…Interestingly, the R-time in swine and rats is similar to previously published values of native TEGs for cats [8]. Reported data for both pigs and rats have shown similar prothombin time (PT) and activated thromboplastin time (APTT) compared to humans [5, 9] (Table 1).…”
Section: Discussionsupporting
confidence: 80%
“…Interestingly, the R-time in swine and rats is similar to previously published values of native TEGs for cats [8]. Reported data for both pigs and rats have shown similar prothombin time (PT) and activated thromboplastin time (APTT) compared to humans [5, 9] (Table 1).…”
Section: Discussionsupporting
confidence: 80%
“…The reference values established in the present study for feline citrated blood using the ROTEM ® delta analyser differ from those of previous studies, which evaluated reference values for viscoelastic measurements of feline blood using the TEG ® 5000 Hemostasis Analyser (Alwood et al, 2004(Alwood et al, , 2007Banerjee et al, 2011;Marschner et al, 2010;Montgomery et al, 2008). Even when focusing only on the non activated tests (to exclude reagent-dependent influences) large differences compared with previous studies cited earlier, but also between the cited studies became obvious.…”
Section: Parametermentioning
confidence: 69%
“…For example, in most cases the present study investigated shorter CT and CFT values and greater MCF and α values. Only Alwood et al (2004) and Banerjee et al (2011) published shorter reaction times (R; corresponding to CT) and Alwood et al (2004) also found shorter K values (corresponding to CFT). The fact that ROTEM ® delta showed shorter CT and CFT and greater MCF and α-values for feline blood than the TEG ® 5000 Hemostasis Analyser is well in accordance with a previous human study which directly compared both instruments (Nielsen, 2007).…”
Section: Parametermentioning
confidence: 92%
See 1 more Smart Citation
“…The addition of activators decreases TEG variability in some species, although this has been an inconsistent finding in studies of healthy cats. 6,7 Kaolin activates in vitro coagulation primarily via the intrinsic or contact-activated pathway, while TF activates in vitro coagulation via the extrinsic or FVII:TF pathway. 8 This explains the difference between the TEG tracings in the cats with FXII deficiency described herein.…”
Section: Discussionmentioning
confidence: 99%